1997
DOI: 10.1577/1548-8659(1997)126<0144:mcimsf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Concentrations in Maine Sport Fishes

Abstract: To assess mercury contamination of fish in Maine, fish were collected from 120 randomly selected lakes. The collection goal for each lake was five fish of the single most common sport fish species within the si/e range commonly harvested by anglers. Skinless, boneless fillets of fish from each lake were composited, homogenized, and analyzed for total mercury. The two most abundant species, brook trout Salvelinusfontinalis and smallmouth bass Micropterusdolomieu. were also analyzed individually. The composite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
2
22
2
1
Order By: Relevance
“…Previous studies of smallmouth bass demonstrated increasing Hg concentrations with size, age, or both (May et al 2000;Neumann and Ward 1999;Stafford and Haines 1997). However, and contrary to expectations, concentrations in our fish were poorly correlated with fish size and age.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies of smallmouth bass demonstrated increasing Hg concentrations with size, age, or both (May et al 2000;Neumann and Ward 1999;Stafford and Haines 1997). However, and contrary to expectations, concentrations in our fish were poorly correlated with fish size and age.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, previously reported Hg concentrations in smallmouth bass from the Big River were lower than in the Current and Eleven Point rivers, which agrees with the lower concentrations in our samples from site 6 ( Table 3). The concentrations in our fish therefore appear typical for Missouri smallmouth bass, but they are lower than those in smallmouth bass from some other areas of the United States (e.g., Brumbaugh et al 2001;May et al 2000;Mueller and Serdar 2002;Neumann and Ward 1999;Stafford and Haines 1997;USEPA 2001). Concentrations in most of our fish exceeded the nationwide mean of 0.34 lg/g ww for smallmouth bass (USEPA 2001), but none approached the maximum reported by the USEPA (>5 lg/g ww).…”
Section: Discussionmentioning
confidence: 48%
“…The fish tissue results also suggest that Hg concentrations in most fish species, with the exception of smallmouth bass, are generally lower on MDI than in other regions of Maine (Stafford & Haines, 1997;Burgess, 1997). Hg concentrations in lake trout from MDI ranged 0.21-0.32 渭g/g ww, which is considerably lower than the statewide mean of 0.45 渭g/g ww (Stafford & Haines, 1997). Similarly, Hg concentrations in landlocked salmon from MDI ranged 0.11-0.37 渭g/g ww, whereas the statewide mean for this species is 0.35 渭g/g ww (Stafford & Haines, 1997).…”
Section: Fishmentioning
confidence: 78%
“…The relationship between age and Hg concentration has been well documented in fish (e.g., lake whitefish, walleye, northern pike, and lake trout; Jackson, 1991;Evans et al, 2005). Stafford and Haines (1997) found that in particular, age and Hg concentrations were strongly positively correlated in non-salmonid fish species. There are, however, instances where concentrations do not change or actually decrease with age/size, likely due to dietary shifts to herbivory (e.g., some tropical fishes; da Silva et al, 2005).…”
Section: Growth Rates and Lifespan Of Organismsmentioning
confidence: 95%